1999
DOI: 10.1002/1529-0131(199909)42:9<1936::aid-anr20>3.0.co;2-k
|View full text |Cite
|
Sign up to set email alerts
|

Induction of ?1-antitrypsin synthesis in human articular chondrocytes by interleukin-6-type cytokines: Evidence for a local acute-phase response in the joint

Abstract: Objective. We have previously shown that human articular chondrocytes synthesize large amounts of interleukin-6 (IL-6) upon stimulation with proinflam-matory cytokines and that they express the IL-6 receptor. The present study was undertaken to analyze whether different IL-6-type cytokines can induce synthesis of the acute-phase protein 1-antitrypsin in human articular chondrocytes. Methods. Chondrocytes from human articular cartilage, cultured in agarose, were stimulated with IL-6-type cytokines. Total RNA wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 58 publications
0
18
0
Order By: Relevance
“…For example, in lung-derived epithelial cells (HTB 58), in lung adenocarcinoma cells (HTB 55) and in human alveolar epithelial cells neither IL-1b nor IL-6 had any influence on a1-PI secretion [3,31,32]. In contrast, a1-PI release was found to be enhanced by those cytokines in hepatocytes, cornea cells, articular chondrocytes and monocytes/macrophages [4,5,33,34]. Taken together, these data could imply that the absence of the effect of IL-1b and IL-6 on a1-PI release might be specific for alveolar and intestinal epithelial cells.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…For example, in lung-derived epithelial cells (HTB 58), in lung adenocarcinoma cells (HTB 55) and in human alveolar epithelial cells neither IL-1b nor IL-6 had any influence on a1-PI secretion [3,31,32]. In contrast, a1-PI release was found to be enhanced by those cytokines in hepatocytes, cornea cells, articular chondrocytes and monocytes/macrophages [4,5,33,34]. Taken together, these data could imply that the absence of the effect of IL-1b and IL-6 on a1-PI release might be specific for alveolar and intestinal epithelial cells.…”
Section: Discussionmentioning
confidence: 98%
“…a1-PI is primarily a liver-derived serum protein with a molecular weight between 52 and 55 kDa. Recent studies showed that a1-PI is also synthesized outside the liver: by alveolar epithelial cells [3], monocytes [4], chondrocytes [5], human cornea [6] and, of importance for local control of inflammatory processes in the gut, in intestinal epithelial cells [7].…”
Section: Introductionmentioning
confidence: 99%
“…In human neutrophils, monocytes, alveolar macrophages and intestinal epithelial cells, AAT expression increases in response to inflammatory mediators such as lipopolysaccharide, TNFa, interleukin (IL)-1, IL-6, and the complex of AAT and neutrophil elastase. [16][17][18][19] Increasing evidence indicates that the anti-inflammatory properties of AAT may allow for it to serve as a therapeutic agent for altering the immune response. For example, AAT delivery can completely abolish acute inflammatory infiltration and connective tissue breakdown.…”
Section: Introductionmentioning
confidence: 99%
“…5). AAT may facilitate the survival of islet transplants in engrafted patients, because the inhibitor prevents inflammatory cytokine production, blocks immune cell infiltration and function, inhibits complement activation, and delays the development of diabetes in nonobese diabetic mice (5)(6)(7)(8)(9)(10)(11)(12).…”
mentioning
confidence: 99%